2004
DOI: 10.1128/jb.186.16.5460-5472.2004
|View full text |Cite
|
Sign up to set email alerts
|

The LuxR Homolog ExpR, in Combination with the Sin Quorum Sensing System, Plays a Central Role in Sinorhizobium meliloti Gene Expression

Abstract: Quorum sensing, a population density-dependent mechanism for bacterial communication and gene regulation, plays a crucial role in the symbiosis between alfalfa and its symbiont Sinorhizobium meliloti. The Sin system, one of three quorum sensing systems present in S. meliloti, controls the production of the symbiotically active exopolysaccharide EPS II. Based on DNA microarray data, the Sin system also seems to regulate a multitude of S. meliloti genes, including genes that participate in low-molecular-weight s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

15
163
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 124 publications
(179 citation statements)
references
References 71 publications
15
163
1
Order By: Relevance
“…For this purpose, we determined promoter activities of several ExpRregulated genes in the WT and sinI strains and their fadL mutant derivatives grown without addition of AHLs to the cultures. Promoter activities of wgeA, wggR, SMc04171, and SMa2111, known to be activated by ExpR and AHLs (17,19), were decreased in the fadL strain ( Fig. 3A and SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…For this purpose, we determined promoter activities of several ExpRregulated genes in the WT and sinI strains and their fadL mutant derivatives grown without addition of AHLs to the cultures. Promoter activities of wgeA, wggR, SMc04171, and SMa2111, known to be activated by ExpR and AHLs (17,19), were decreased in the fadL strain ( Fig. 3A and SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous transcriptome studies detected negative regulation of fadL Sm by expR independent of sinI (17,22). We applied a fadL promoter-EGFP fusion to monitor fadL expression levels.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…meliloti possesses a quorum-sensing system composed of two transcriptional regulators, SinR and ExpR, and the SinRcontrolled autoinducer synthase SinI, which is responsible for the biosynthesis of AHLs (43,44). These AHLs, in conjunction with the ExpR regulator, control a variety of downstream genes (34). Work in our laboratory has shown that the ExpR/ Sin system induces the production of both succinoglycan and EPS II and plays an important role in adjusting motility and chemotaxis in response to cell population density (34,35,42).…”
mentioning
confidence: 99%